The Influence of Green Entrepreneurial Passion, Green Motivation, and Environmental Awareness on Green Entrepreneurial Intentions - Muhammad Ni’mal Maula; Audita Nuvriasari (Arthatama: Journal of Business Management and Accounting, 2026)
This study aims to analyze the effects of green entrepreneurial passion, green motivation, and environmental awareness on green entrepreneurial intention. The sample in this study consisted of 390 respondents, comprising university students from across Indonesia. The data collection technique employed was purposive sampling, using a research instrument in the form of a questionnaire distributed online via Google Forms. The results of the instrument test indicated that the data in this study were valid and reliable. The classical assumption test showed that the data were normally distributed. The findings of this study demonstrate that green entrepreneurial passion has a positive and significant effect on green entrepreneurial intention. This means that the higher the level of students’ enthusiasm and concern for green entrepreneurship, the stronger their intention to engage in entrepreneurship. Green motivation has a positive and significant effect on green entrepreneurial intention. This indicates that stronger environmental drive and commitment increase the intention to pursue environmentally friendly entrepreneurship. Environmental awareness does not have a positive and significant effect on green entrepreneurial intention. This finding suggests that although students may have high awareness of environmental issues, such awareness does not translate into entrepreneurial intention if it is not accompanied by concrete action.